Upaya Meningkatkan Partisipasi dan Hasil Belajar Materi Pertumbuhan dan Perkembangan Makhluk Hidup melalui Penerapan Model Pembelajaran Kooperatif Tipe STAD Berbantuan Wordwall pada Peserta Didik Kelas III A SD Negeri 11 Mataram - Nurul Fitriani; I Nyoman Karma; Diani Pratiwi (Mataram University, 2026)
This study aimed to examine the implementation of the Student Teams Achievement Division (STAD) cooperative learning model supported by Wordwall media in improving students’ participation and learning outcomes. The research subjects consisted of 25 third-grade students of class IIIA at SD Negeri 11 Mataram. This study employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model, which includes the stages of planning, acting, observing, and reflecting, and was conducted over two learning cycles. The research instruments comprised observation sheets and individual evaluation tests. The results indicated an improvement in students’ learning participation. The level of learning participation in the pre-cycle stage was 59%, which increased to 74% in the first cycle and further rose to 87% in the second cycle. The increase in learning participation had a positive impact on students’ learning outcomes, which showed progressive improvement. In the pre-cycle stage, the average learning outcome score was 73. This score increased to an average of 80.5 in the first cycle and showed a significant improvement to 86 in the second cycle. Based on these findings, the STAD cooperative learning model assisted by Wordwall media can serve as an effective solution to enhance student participation and create an enjoyable learning environment during the learning process, thereby improving learning outcomes.